An Analysis of the Economic Dimensions of Entrepreneurship in Surah Al-Kahf - Siregar, Dahrul; Ichsan, Reza Nurul (UPT Publikasi Ilmiah UNISBA, 2024)
This paper analyzes Shah’s examination of entrepreneurial traits exemplified by the Companions of the Cave in Qur’anic Surah Al-Kahf verses 13-14. A literature review synthesizes existing research exploring Islamic entrepreneurial orientations derived from theology. The study employs qualitative methodology in categorizing entrepreneurial dimensions mentioned in the two ayat based on Shah’s framework highlighting ambition, risk-taking, resilience and spirituality. The traits are then analyzed against predominant entrepreneurship theory literature focused on opportunity recognition, resource leveraging and perseverance competencies. Findings suggest alignment between conventional and Qur’anic foundations in many aspects, though divergences exist regarding motivation sources driving enterprise. Practical implications propose integrating spiritual identity and purpose more strongly into entrepreneurship education programs to nurture morality-centered ambitions grounded in religious scripture.